2013
DOI: 10.1038/nature12296
|View full text |Cite
|
Sign up to set email alerts
|

The linear ubiquitin-specific deubiquitinase gumby regulates angiogenesis

Abstract: A complex interplay of signaling events, including the Wnt pathway, regulates sprouting of blood vessels from preexisting vasculature during angiogenesis. Here we show that two distinct mutations in the (uro)chordate-specific Gumby/Fam105b gene cause an embryonic angiogenic phenotype in gumby mice. Gumby interacts with Disheveled 2 (Dvl2), is expressed in canonical Wnt-responsive endothelial cells and encodes an Ovarian Tumor Domain (OTU) class of deubiquitinase (DUB) that specifically cleaves linear ubiquitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
353
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(369 citation statements)
references
References 46 publications
14
353
1
1
Order By: Relevance
“…Mice deficient in LUBAC subunits have variable degrees of inflammation, from a mild phenotype in HOIL-1-deficient mice (16) to more severe inflammation and dermatitis in SHARPIN KO (2,17) to defective vascularization and embryonic lethality in HOIP KO (18). Consistent with the essential function of OTULIN in regulation of multiple signaling pathways, OTULINdeficient mice (gumby/gumby) are embryonic lethal due to vascular and neuronal defects caused by dysregulation in canonical Wnt signaling (8).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Mice deficient in LUBAC subunits have variable degrees of inflammation, from a mild phenotype in HOIL-1-deficient mice (16) to more severe inflammation and dermatitis in SHARPIN KO (2,17) to defective vascularization and embryonic lethality in HOIP KO (18). Consistent with the essential function of OTULIN in regulation of multiple signaling pathways, OTULINdeficient mice (gumby/gumby) are embryonic lethal due to vascular and neuronal defects caused by dysregulation in canonical Wnt signaling (8).…”
Section: Discussionmentioning
confidence: 77%
“…Although OTULIN functions exclusively as a Met1 deubiquitinase (7,8), CYLD may also hydrolyze Lys63-linked ubiquitin (9). OTULIN is an evolutionarily highly conserved protein, and in mice complete deficiency is embryonically lethal (8). Recently, we reported patients with heterozygous germline mutations in TNFAIP3/ A20 (10), which has DUB activity for K63-linked polyubiquitin chains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that OTULIN exclusively hydrolyzes Met1-Ub, prevents accumulation of Met1-Ub on LUBAC components under basal conditions, and restricts ubiquitination of LUBAC substrates after receptor stimulation [2][3][4]. However, the contribution of OTULIN to regulation of physiological immune responses had not been investigated.…”
mentioning
confidence: 99%
“…Met1-Ub chains are assembled by the linear ubiquitin chain assembly complex (LU-BAC), composed of HOIP, HOIL-1, and SHARPIN [1]. LUBAC function is regulated by the deubiquitinases (DUBs) OTULIN [2-4] and CYLD [5][6][7], which both associate with the catalytic subunit HOIP [5][6][7][8].Previous studies have revealed that OTULIN exclusively hydrolyzes Met1-Ub, prevents accumulation of Met1-Ub on LUBAC components under basal conditions, and restricts ubiquitination of LUBAC substrates after receptor stimulation [2][3][4]. However, the contribution of OTULIN to regulation of physiological immune responses had not been investigated.…”
mentioning
confidence: 99%